RANCANG BANGUN APLIKASI MULTIMEDIA 3 DIMENSI MUSEUM LAMBUNG MANGKURAT BANJARBARU - Selvia Indah Liany Abdie; Dodon T. Nugrahadi; Fatma Indriani (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2015)
Along with the development of technology, the museum is required to use use of technology in dissemination of information. One of the transfer of information technology in the technology is multimedia. So, it's necessary media dissemination of information that will be packaged attractively information about museum that is in the form 3 dimension. The aim of this research is to know whether Multimedia application 3 Dimensional facility as information and The Introduction Lambung Mangkurat Museum can support government program in National Movement Love Museum. Based on the results of research is known that the application can support government program in National Movement Love Museum through Museum in school, where the aim is to introduce museum and museum collection that is in the students. Keywords : Museum, Multimedia, 3 Dimension. Seiring dengan perkembangan teknologi, museum dituntut menggunakan pemanfaatan teknologi dalam penyampaian informasi. Salah satu teknologi dalam penyampaian informasi tersebut adalah teknologi multimedia. Sehingga, diperlukan media penyampaian informasi yang dikemas dengan menarik mengenai informasi museum yaitu dalam bentuk 3 dimensi. Tujuan dari penelitian ini adalah mengetahui apakah Aplikasi Multimedia 3 Dimensi sebagai Sarana Informasi dan Pengenalan Museum Lambung Mangkurat dapat mendukung program pemerintah dalam Gerakan Nasional Cinta Museum. Berdasarkan hasil penelitian diketahui bahwa aplikasi ini dapat mendukung program pemerintah dalam Gerakan Nasional Cinta Museum melalui kegiatan Museum Masuk Sekolah, dimana tujuannya adalah mengenalkan museum dan koleksi yang ada pada museum kepada siswa. Kata kunci : Museum, Multimedia, 3 Dimensi.